The Influence of Augmented Reality-Based Learning Media on Understanding Mathematics Concepts of Fifth-Grade Students - Cahyati, Widia; Doly, Marah (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
The technology known as augmented reality allows the real and virtual (digital) worlds to merge. Specifically, it projects three-dimensional (3D) objects onto the surface of the real world using the medium of a camera, giving the impression that the objects are actually there. This research, thus, aims to find out how fifth-grade students at the State Elementary School of 064005 Medan understand mathematical ideas in relation to augmented reality-based learning materials. The research population was fifty fifth-grade students at the State Elementary School of 064005 Medan. The whole sampling technique was employed to collect research samples. Two classes of the elementary school, namely class V A as the experimental class and class V B as the control class, were the samples used in this research. Based on post-test data, the average learning outcome score for the experimental class was 89.00, while the control class was 79.80. According to research findings, augmented reality-based educational materials exerted a significant impact  (sig. 0.05) on the understanding of mathematical concepts for fifth-grade students, with a percentage of 80.88%, so the students' answers to the augmented reality-based learning media for mathematics concepts for fifth-grade students at the State Elementary School of 064005 Medan can be classified as good. Hence, the use of media is practical and scientifically effective. These results demonstrate that students' responses to augmented reality-based learning media in understanding mathematical concepts in flat-sided geometry material are in a good category. The implication is that teachers can put more emphasis on the use of advanced technological media in understanding concepts and other mathematical skills.